Predicting the relative humidity of allergic asthma using GA - Ismail, Rasha Rokan (Journal of Electrical Engineering and Computer (JEECOM), 2024)
Asthma is a serious chronic disease that affects the airways, and the occurrence of this disease depends on many factors, including psychological ones, and others because of specific foods, and others depend on weather conditions such as the ambient temperature and relative humidity of the air. In this research, the disease was diagnosed by identifying one of its causes, which is air humidity, which is an important factor for exacerbation of asthma, using one of the algorithms of artificial intelligence, which is the genetic algorithms, which depend on the symptoms of the disease and the degree of humidity in the air. Examples were extracted from contaminated and also non-infected individuals, and also the formula was related to them as well as the success price was 95%.